Global marketing translation and localization for French‐speaking countries. Issue 3 (28th August 2019) - Martin, Elizabeth
Abstract: This article explores translation practices in international advertising designed for different French‐speaking countries, highlighting the myriad ways in which global brands reshape their messages to appeal to local markets. A number of factors will determine the specific approach to linguistic and cultural phenomena when adapting a global advertising campaign for local audiences. In addition to the seamless blending of translated content and multimodal language mixing appearing in advertising for these markets, one notices that the degree of French‐English mixing, types of bilingual creativity and glossing techniques differ noticeably across markets, media and product categories. Newer technologies and the social media craze have also had a profound impact on the assimilation of English borrowings.